2014
DOI: 10.1097/wad.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

Practice Effects and Amyloid Deposition

Abstract: Clinical trials in Alzheimer’s disease are moving towards prevention studies in prodromal individuals with amyloid burden. However, methods are needed to identify individuals expected to be amyloid positive for these studies to be feasible and cost effective. The current study sought to determine whether short-term practice effects on cognitive tests can identify those with notable uptake on amyloid imaging. Twenty-five, non-demented older adults (15 cognitively intact, 10 Mild Cognitive Impairment) underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 39 publications
3
21
1
Order By: Relevance
“…Individuals with a global composite of 18F-Flutemetamol SUVR z-score of ≥2.0 were labeled as amyloid positive and those with composites <2.0 were amyloid negative (24). For practice effects, individuals with a mean practice effects z-score across all seven measures of ≤−0.50 were labeled as low practice effect and those with mean z-scores >−0.50 were high practice effects (19). Using this dichotomization strategy, 13 individuals were amyloid positive (48%) and 14 were amyloid negative (52%); 11 had low practice effects (41%) and 16 had high practice effects (59%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with a global composite of 18F-Flutemetamol SUVR z-score of ≥2.0 were labeled as amyloid positive and those with composites <2.0 were amyloid negative (24). For practice effects, individuals with a mean practice effects z-score across all seven measures of ≤−0.50 were labeled as low practice effect and those with mean z-scores >−0.50 were high practice effects (19). Using this dichotomization strategy, 13 individuals were amyloid positive (48%) and 14 were amyloid negative (52%); 11 had low practice effects (41%) and 16 had high practice effects (59%).…”
Section: Resultsmentioning
confidence: 99%
“…Mormino et al (18) reported diminished practice effects across yearly visits in cognitively normal older adults with either beta-amyloid deposition or neurodegeneration on brain imaging compared to older adults without either type of pathology. In another study of older adults with varying levels of cognitive impairment (19), practice effects across one week on a single visual memory test were negatively correlated with β-amyloid neuritic plaque density utilizing PET imaging, with lower practice effects associated with higher amyloid plaque burden. In this same cohort (20), brain metabolism on FDG-PET was significantly correlated with practice effects across one week, even after controlling for baseline cognition.…”
Section: Introductionmentioning
confidence: 99%
“…These change formulae make such methods valuable for clinical trials (e.g., using practice effects to enrich samples with patients showing abnormally low scores). Clinically, smaller than expected practice effects may portend a declining trajectory (Duff et al, 2011), poorer response to an intervention (Duff et al, 2010), or greater risk of Alzheimer’s-related pathology (Duff et al, 2014; Galvin et al, 2005; Mormino et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Although these improvements in test scores may not reflect true change in cognitive abilities, and they have traditionally been dismissed as an artifact of the testing situation, it remains possible that practice effects do inform us about unique aspects of cognition (Duff, Callister, Dennett, & Tometich, 2012). For example, smaller than expected practice effects in older adults may herald a declining trajectory (Duff et al, 2011), poorer response to an intervention (Duff, Beglinger, Moser, Schultz, & Paulsen, 2010), or greater risk of Alzheimer’s-related pathology (Duff, Foster, & Hoffman, 2014; Galvin et al, 2005; Mormino et al, 2014). The potential for practice effects to inform clinicians and researchers about cognitive course, treatment response, and brain pathology has also been examined in neurodegenerative disorders (Duff et al, 2007), traumatic brain injury (Rogers, Fox, & Donnelly, 2015), and stroke (Chiu et al, 2014).…”
mentioning
confidence: 99%
“…Thus, this task was appropriate and safe for probing motor practice effects in this study. Participants were then re-tested a week later on a follow-up trial to identify any measureable practice effects across one week, an approached used previously with other neuropsychological assessments (Duff, 2014; Duff et al, 2008; Duff, Foster, & Hoffman, 2014; Duff et al, 2011). …”
Section: Methodsmentioning
confidence: 99%